2015
DOI: 10.1093/ajae/aav025
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Crop Yield and Acreage to Prices and Climate

Abstract: We investigate the effect of crop price and climate variables on rainfed corn and soybean yields and acreage in the United States using a large panel dataset for the 1977–2007 period. Instrumental variables are used to control for endogeneity of prices in yield and acreage regressions, while allowing for spatially auto‐correlated errors. We find that an increase in corn price has a statistically significant positive impact on corn yield, but the effect of soybean price on soybean yields is not statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
167
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(203 citation statements)
references
References 41 publications
17
167
1
Order By: Relevance
“…The highest yield reductions, 25 % for corn and 19 % for switchgrass, were simulated in response to the high emission RCP8.5 pathway at the end of the century. Lower percentage crop yield reductions were found in this study compared to similar previous research results (e.g., Miao et al, 2015;Ummenhofer et al, 2015;Cai et al, 2009;Schlenker and Roberts, 2008). One possible reason that lower reductions in crop yields were predicted within this study could be the inclusion of CO 2 concentrations during the simulations, and the capability of SWAT to account for positive effects of CO 2 concentration on crop yield.…”
Section: Crop Yieldssupporting
confidence: 72%
“…The highest yield reductions, 25 % for corn and 19 % for switchgrass, were simulated in response to the high emission RCP8.5 pathway at the end of the century. Lower percentage crop yield reductions were found in this study compared to similar previous research results (e.g., Miao et al, 2015;Ummenhofer et al, 2015;Cai et al, 2009;Schlenker and Roberts, 2008). One possible reason that lower reductions in crop yields were predicted within this study could be the inclusion of CO 2 concentrations during the simulations, and the capability of SWAT to account for positive effects of CO 2 concentration on crop yield.…”
Section: Crop Yieldssupporting
confidence: 72%
“…Although conceptually higher prices may also lead to expansion of acreage under cultivation of a crop to a less fertile land, and hence reducing yield, several empirical studies have shown that the positive effect outweighs this negative effect (Haile et al 2016;Miao et al 2016). Crop price volatility, on the other hand, acts as a disincentive for production because it introduces output price risk.…”
Section: Price Change and Volatilitymentioning
confidence: 99%
“…Given these patterns we would expect a non-linear relation with production. Some empirical evidence shows that population density reduces crop supply (Miao et al 2016). …”
Section: Price Change and Volatilitymentioning
confidence: 99%
See 2 more Smart Citations